Sense of Agency, Affectivity and Social-Ecological Degradation: An Enactive and Phenomenological Approach - Siqueiros-García, Jesús M.; Manuel-Navarrete, David; Eakin, Hallie; Mojica, Laura; Charli-Joseph, Lakshmi; Pérez-Belmont, Patricia; Ruizpalacios, Beatriz (Frontiers in Psychology, 2022)
In the last few years, there has been an interest in understanding the impact of environmental change and degradation on people's affective life. This issue has become particularly pressing for populations whose form of life is heavily dependent on ecosystem services and functions and whose opportunities for adaptation are limited. Based on our work with farmers from the Xochimilco urban wetland in the southwest of Mexico City, we begin to draw a theoretical approach to address and explain how environmental degradation impacts people’s affective life and sense of agency. Farmers who were part of our project referred to a sense of despair and helplessness towards the loss of the ecosystem and their traditional farming-based form of life. From the perspective of phenomenology, enactivism and ecological psychology, we argue that the loss of this form of life in the area is related to the degradation of socio-ecological systems, limiting the opportunities for people to relate meaningfully to others and the environment. We posit that losing meaningful interaction with the environment generates a feeling of loss of control while leading farmers to feel frustrated, anxious and stressed. Such affective conditions have a direct impact on their sense of agency. In terms of adaptation, the negative interaction between degradation, affective states and a diminished sense of agency can create a downward spiral of vulnerability, including political vulnerability.